Mechanism of Power Quality Deterioration Caused by Multiple Load Converters for the MVDC System - Huang, Heming; Liu, Fei; Zha, Xiaoming (Frontiers in Energy Research, 2022)
Medium Voltage Direct Current (MVDC) systems are widely used in ship power distributed systems, wind farms and photovoltaic power plants. With the increasing of load converters interfacing into the MVDC system, the power quality may deteriorate. Researches on factors affecting MVDC power quality are very few and effect caused by multiple load converters are often neglected. In this paper, the mechanism of power quality deteriorating caused by interfacing multiple load converters on MVDC system has been discussed. Impedance model of MVDC system is developed with the state space averaging method and the small-signal analysis method. The three-level H-bridge DC/DC converter is employed as load converter. As a result of theoretical analysis, the more load converters connecting to The MVDC system, the more fragile the MVDC system is to background harmonics. Both simulation and experiment are implemented to verified this conclusion.